Visualisasi Bunga Teratai Sebagai Objek Dalam Karya Batik Tulis Dikombinasi Dengan Teknik Sulam - Yuni Mairiza; Eliya Pebriyeni (Institut Nalanda, 2024)
The aim of making the final work is to visualize the beauty of lotus flowers with various colors in the form of women's clothing, the idea of which comes from the type of lotus flower. The technique that the author uses to make this clothing is a combination of written batik and embroidery techniques. Currently, MSMEs in West Sumatra are increasingly selling hand-written batik clothing. This is the driving force for the author in creating craft works in the form of clothing using different techniques. The combination of written batik and embroidery techniques is also an idea for business people in West Sumatra in promoting local products. The creation method in this final work is carried out in stages, namely: the preparation stage is an observation related to the initial idea of the author's interest, elaboration is the in-depth stage and displays the beauty of the lotus flower as viewed from the internet site, a collection of images and field surveys, synthesis is the creation of an idea for a work, concept realization is a stage of the work process and completion or finishing of the work. Based on the method used, works were created in the form of women's clothing with lotus flower motifs using written batik techniques combined with embroidery techniques. The author created seven works in the form of clothing with the titles: Nymphaea Padma, Nymphaea tropical, Nymphaea stellate, Nymphaea caerulea, Nymphaea heudeloti, Nymphaea capensis, Nymphaea mexiana.